Accessibility of district health nursing services in the greater Bronkhorstspruit - E O Mashia; N C van Wyk (AOSIS, 2004)
A growing concern about the decline in the number of non-Black patients making use of the Bronkhorstspruit Clinic exists. Opsomming Toenemende kommer bestaan oor die afname in die getal nie-Swart pasiënte wat van die Bronkhorstspruit Kliniek gebruik maak. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.